KEPEMIMPINAN DEMOKRATIS KIAI PESANTREN (STUDI DI PONDOK PESANTREN MAMBAUL ULUM CENTREN PANGTONGGAL PAMEKASAN) - Akhmad Fauzi Sayuti (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
The governance transformation of Islamic boarding schools (pesantren) in the contemporary era demands a leadership model capable of synergistically reconciling classical Islamic values with the imperatives of modern organizational management. The gradual shift from centralized authority structures toward more participatory and inclusive approaches has emerged as a strategic concern in sustaining the institutional development of Islamic educational institutions. This study aims to characterize the democratic leadership practices of the kiai, examine the facilitating and constraining factors of its implementation, and assess its consequential impact on the institutional advancement of Pondok Pesantren Mambaul Ulum Centren Pangtonggal Pamekasan. A qualitative methodology was employed through a case study design, utilizing in-depth interviews, participatory observation, and documentary analysis, with validity established via source and methodological triangulation. The findings reveal that the democratic leadership of the kiai manifests across six practical dimensions: institutional deliberation (musyawarah), authority delegation, bidirectional communication, moral exemplariness, administrative transparency, and human resource empowerment. This model constitutes a meaningful synthesis of the Islamic values of syura, justice, and amanah with the principles of participatory, transformational, and ethical leadership, ultimately producing a pesantren governance framework that is inclusive, accountable, and adaptive, while preserving the spiritual legitimacy of the kiai as the institution's central authority.